Development of Polyherbal Shampoo for Antifungal Activity and its Comparison with Commercially Available Shampoo: A Research Article - Patidar, Dr. Kalpana (Asian Journal of Pharmaceutics (AJP), 2018)
Background: The study aimed to formulate a pure herbal shampoo, evaluate, and compare its physicochemical properties with the marketed synthetic and marked herbal shampoos. Materials and Methods: The herbal shampoo formulated by adding the extracts of different herbs such as pomegranate, neem, hibiscus, shikakai, reetha, curry leaves, licorice, and orange peel. Small amount of methylparaben has been added as a preservative and pH adjusted with citric acid. Shampoo formulations were tested against fungus Malassezia furfur by agar well diffusion method. Results: The formulated herbal shampoo was clear and appealing. It showed good cleansing and detergency, low surface tension, small bubble size, and good foam stability after 5 min. The prepared shampoo and commercial shampoos showed comparable results for percent solid contents also. Conclusion: The results indicated that the formulated shampoo is having excellent, at par with commercially available shampoo. However, further, research and development are required to improve its quality and safety.